KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN KOPERASI KARYAWAN - Soelistiani Soegiono; Heru Suprihhadi (Journal of Management and Business, 2007)
Cooperative enterprise core values are the spirit of togetherness, mutual cooperation and solidarity among its members. Owning only millions of rupiah at the beginning, cooperative enterprise has been growing and spreading their business rapidly, and nowadays coperative enterprise has billions of rupiah as its capital. The key for its success is the quality of service. Increasing the service quality will be encouraging the participation and support from the members. This fact has led to the escalation of number of its member and capital. The effect of service quality to cooperative enterprise member’s satisfaction is the main study and topic of this research. Cluster random sampling method has been chosen to collect the data from 94 members. The questionnaire was based on the following five dimensions namely tangibles, reliability, responsiveness, assurance and empathy. While the questionnaire corresponding to the member’s satisfaction was derive from two values, which are related to purchase and service. The data was compared and processed by linier regression. The result is t (testing coefficient) equal to 16,248 which revealed that the effect of service quality to the member’s satisfaction is significant and convincing in Financial Service Business Unit.